Rubber Production and Physiological Characters on Stimulation and Fertilizer Effect - Risal Ardika (AGRIVITA, Journal of Agricultural Science, 2023)
Rubber is one of the important commodities of the Indonesian economy. Nowadays, efforts to increase rubber production in Indonesia are done through increased innovation such as good planting material and using stimulant application. Superior rubber clones have varied performance and metabolism and their response to stimulants are varies. Stimulants application should be refered to plant physiological properties which is associated with latex forming metabolism. The use of superior rubber clones requires higher amount of fertilizer. The use of high yield clones will increase nutrients depletion from the soil, which in turn requires higher additional nutrients through fertilization. Fertilization done in based on nutrient analysis will give positive results on latex production and health of rubber plants. This study was conducted to assess the to evaluate ethephon stimulation and fertilization on latex yield production and physiological latex on different clones. This study was conducted in an experimental field situated at 2.9275° South and 104.5386° East of Indonesian Rubber Research Institute in South Sumatra. The experiment was laid out in Split Plot Design with 3 replications. The main plot is the rubber clones and sub plots are fertilization rate and ethephon stimulation. The rubber clones for this research i.e GT 1, BPM 24, PB 260 and IRR 112 were situated on the existing rubber plantation and planted in 2011 with 6 x 3 m planting spacing. Different fertilization rates were used in the experiment such as control (without fertilizer), 50% recommended rate (50 RR), 100% recommended rate (100 RR), and 150% recommended rate (150 RR). Ethephon stimulation was applied every two months during the observation period with a rate of S/2 d3 ET2.5% 6/y. Various parameters that were determined for this research study i.e: latex yield, physiological latex (sucrose, inorganic phosphorus, and thiol) and tapping panel dryness. Results showed that rubber yield such as latex production and dry rubber content were significantly affected by fertilization and ethephon stimulation. Latex characteristics of latex such as thiol, inorganic phosphate and sucrose were graded at an optimal range upon fertilization.